Desorption of phosphate from three Finnish mineral soil samples during adsorption of vanadate, molybdate and tungstate - Mikkonen, Anneli; Tummavuori, Jouni (Agricultural Research Centre of Finland, 1994)
Tutkittaessa molybdaatin, vanadaatin ja volframaatin adsorptiota kolmeen suomalaiseen mineraalimaanäytteeseen 10-4 tai 10-5 M liuoksesta mitattiin myös adsorption aikana liuosfaasiin siirtyneen fosforin määriä. Adsorption etenemistä ja fosfaatin desorptiota seurattiin ajan funktiona kunkin maan luonnollisessa pH:ssa. Toisessa kokeessa mitattiin desorboitunut fosfori, kun tutkittiin vanadaatin, molybdaatin ja volframaatin adsorptiota 72 tunnin aikana pH-alueella 2,3-7,5. Tulokset osoittivat, että molybdaatin, volframaatin ja vanadaatin läsnäolo pyrkii lisäämään liuosfaasissa olevan fosforin määrää. Artikkelissa tarkastellaan lyhyesti myös molybdeenin, vanadiinin ja volframin ionimuotoja vesiliuoksissa

Adsorption of V(V) and MO(VI) from 10-4 M and 10-5 M solutions and W(VI) from a 10-4 M solution (in 0.02 M KC1) by three Finnish mineral soils was studied in two series of experiments. In the first experiment, the adsorption of V, Mo and W by soil and the desorption of P were measured at the soils' natural pH after an equilibration time of 3, 5, 22, 29, 46 and 70 h. Adsorption of molybdate occurred mainly within the three first hours, whereas adsorption of vanadate and tungstate were slower processes. During the first few hours, the presence of molybdate seemed to increase the desorption of phosphate most effectively, but after a longer equilibration period, the differences between additions of V, Mo, and W became smaller. In the second experiment, the adsorption process was followed as a function of the acidity of the suspension (pH 2.3-7.5; for W pH 2.8-7.5). Adsorption of V(V), MO(VI) or W(VI) resulted in a statistically significant increase in the amounts of P desorbed from all three soils over the pH range studied.
Keywords: Ka; savi; anionit; fosfori; clay; finesand; anions; polyanions; specific adsorption